Sistem Monitoring Presensi Dosen Berbasis RFID Menggunakan Teknologi E-KTP - Saputra, Made Yosfin; Santiyasa, I Wayan (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 12 No 1 (2023): JELIKU Volume 12 No 1, August 2023DO - 10.24843/JLK.2023.v12.i01.p14, 2023)
The influence of COVID-19 has changed people's habits towards new habits or called the new normal. This influence changes daily activities into online and offline activities or hybrid activities. Activities at the University are one of the impacts that are influenced by this new habit. This causes students to always make sure each activity schedule is available. The implementation of the hybrid system is certainly implemented by the lecturers, so students need to always know the presence of the lecturer. Therefore, a lecturer attendance monitoring system is needed to find out information on the presence of lecturers. RFID is an autoID that can be used to record and be a medium to inform about the presence of lecturers. Google Spreadsheet and Google Data Studio are media for data management and interfaces to display lecturer attendance data in a concise and practical but real-time manner. The use of e-KTP makes it easier to input data, where in addition to being an RFID tag, e-KTP is also an item that is always carried and does not require the purchase of an RFID tag card again.